The French connection: Some Icelandic translations of French literature in manuscript and print, ca. 1400-1900 - Matthew James Driscoll (Tabularia)
The extent of manuscript production in medieval Iceland is well known; less well known is that manuscript transmission remained the norm in Iceland well into the modern era, long after the arrival of the printing press. The range of types of literary works preserved in these manuscripts is vast. Although the bulk of this literature was indigenous and in Icelandic, many works were translated, too, both from Latin and the various European vernaculars. The present essay examines a few of the French literary works that survive in Icelandic translations, both in manuscript and print, from Thomas’s Tristan to Jules Verne.